Combination of gallium citrate and levofloxacin induces a distinct metabolome profile and enhances growth inhibition of multidrug-resistant Mycobacterium tuberculosis compared to linezolid - Ilchenko, Oleksandr; Nikolaevskaya, Elena; Zinchenko, Oksana; Ivanytsia, Volodymyr; Prat-Aymerich, Cristina; Ramstedt, Madeleine; Rzhepishevska, Olena (Frontiers in Microbiology, 2024)
IntroductionTuberculosis (TB) treatment typically involves a tailored combination of four antibiotics based on the drug resistance profile of the infecting strain. The increasing drug resistance of Mycobacterium tuberculosis (Mtb) requires the development of novel antibiotics to ensure effective treatment regimens. Gallium (Ga) is being explored as a repurposed drug against TB due to its ability to inhibit Mtb growth and disrupt iron metabolism. Given the potential interactions between Ga and established antibiotics, we investigated how a combination of Ga with levofloxacin (Lfx) or linezolid (Lzd) affects the growth and metabolome of a multidrug-resistant (MDR) Mtb clinical strain.MethodsMtb was cultured using a BACTEC 960 system with concentrations of Ga ranging from 125 to 1,000 μM and with 250 to 500 μM of Ga combined with 0.125 mg/L of Lfx or Lzd. For metabolome analysis, the antibacterials were used at concentrations that inhibited the growth of bacteria without causing cell death. Metabolites were extracted from Mtb cells and analyzed using chromatography-mass spectrometry.ResultsThe MDR Mtb strain exhibited a dose-dependent response to Ga. Notably, the enhancement in growth inhibition was statistically significant for the Ga/Lfx combination compared to Ga alone, while no such significance was observed for Ga/Lzd. Moreover, exposure to Ga/Lfx or Ga/Lzd resulted in distinct metabolite profiles. Ga treatment increased the level of aconitate, fumarate, and glucose in the cells, suggesting the inhibition of iron-dependent aconitase and fumarate hydratase, as well as disruption of the pentose phosphate pathway. The levels of glucose, succinic acid, citric acid, and hexadecanoic acid followed a similar pattern in cells exposed to Ga and Ga/Lfx at 500 μM Ga but exhibited different trends at 250 μM Ga.DiscussionIn the presence of Lfx, the Mtb metabolome changes induced by Ga are more pronounced compared to those observed with Lzd. Lfx affects nucleic acids and transcription, which may enhance Ga-dependent growth inhibition by preventing the metabolic redirection that bacteria typically use to bypass iron-dependent enzymes.